2021
DOI: 10.1007/s00432-021-03542-5
|View full text |Cite
|
Sign up to set email alerts
|

Using ultrasound-targeted microbubble destruction to enhance radiotherapy of glioblastoma

Abstract: Objective To investigate the efficacy and mechanism of ultrasound-targeted microbubble destruction (UTMD) combined with radiotherapy (XRT) on glioblastoma. Methods The enhanced radiosensitization by UTMD was assessed through colony formation and cell apoptosis in Human glioblastoma cells (U87MG). Subcutaneous transplantation tumors in 24 nude mice implanted with U87MG cells were randomly assigned to 4 different treatment groups (Control, UTMD, XRT, and UTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The momentary formation of minute perforations on the cell membrane surface enhances the permeability of the cell membrane, thus improving the e ciency of delivering plasmids or drugs. Furthermore, the tremendous energy unleashed by transient cavitation is capable of obliterating microvessels within tumor tissues, rendering it a subject of keen interest in the realm of gene therapy and tumor treatment 11,12 . In this research, the application of adjusted ultrasonic parameters, such as MI and repetitive pulse frequency, allowed for the generation of low-energy steady-state cavitation.…”
Section: Discussionmentioning
confidence: 99%
“…The momentary formation of minute perforations on the cell membrane surface enhances the permeability of the cell membrane, thus improving the e ciency of delivering plasmids or drugs. Furthermore, the tremendous energy unleashed by transient cavitation is capable of obliterating microvessels within tumor tissues, rendering it a subject of keen interest in the realm of gene therapy and tumor treatment 11,12 . In this research, the application of adjusted ultrasonic parameters, such as MI and repetitive pulse frequency, allowed for the generation of low-energy steady-state cavitation.…”
Section: Discussionmentioning
confidence: 99%
“…However, relevant studies about the effect of UTMD on the radiotherapy response of glioma are currently rare. In 2021, Peng et al [ 30 ] first confirmed that UTMD improves the destructive effect of IR on glioblastoma in a subcutaneous tumor model in nude mice, which demands to be further validated in an animal model in situ that can recapitulate various aspects of disease more accurately. Accordingly, in the present study, we established an orthotopic mouse glioblastoma model and found, for the first time, that UTMD markedly enhanced the radiosensitivity and prolonged the survival of orthotopic glioblastoma-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, UTMD was performed as described before with some modifications [ 30 ]. As shown in Additional file 1 : Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The SonoVue™ (Bracco, Milan, Italy) microbubbles encapsulating sulfur hexafluoride gas (SF6) were made following the manufacturer's recommendations (18). Before ultrasound treatment, 500 μL of freshly made microbubbles were mixed with medium (0.01%, v/v) and inverted for several minutes to allow the microbubbles to have a close touch with cells.…”
Section: Methodsmentioning
confidence: 99%
“…After 3% (v/v) microbubbles were added, cells were immediately treated with the 1-MHz probe for 1 min under the condition of duty cycle of 20% and peak negative pressure of 0.3 w/cm 2 . Next, the cells were incubated for 24 h. Subsequently, cells were irradiated using an irradiation cabinet (Primus, Siemens, Germany) at a dose of 5 or 10 Gy at a dose rate of 300 cGy/min and an energy of 6 MV (18). Afterwards, cells were used for the following MTT and colony-formation assays as well as western blot and flow cytometry analyses.…”
Section: Methodsmentioning
confidence: 99%